Ultrahigh-temperature ceramic composite powder with core silicon carbide and shell and preparation method thereof
Patent Information
- Application Number
- CN202510562872.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2026-10-30
AI Technical Summary
为了混合均匀需要进一步球磨或混料工艺来处理混合粉体,另外添加碳化硅的晶粒尺寸调控范围窄
本发明通过正硅酸乙酯水解在超高温陶瓷粉体颗粒表面包裹一层二氧化硅层,再通过间二苯酚和甲醛的缩聚反应在二氧化硅层外围包裹一层有机碳,室温“一锅法”获得预烧粉体,最后通过高温裂解和碳热还原反应获得超高温陶瓷为核碳化硅为壳的复合粉体。
Smart Images

Figure CN123003301A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ceramic powder preparation technology, specifically relating to an ultra-high temperature ceramic core and silicon carbide shell composite powder and its preparation method. Background Technology
[0002] Ultra-high temperature ceramics comprise transition metal carbides (TiC and ZrC, etc.), transition metal diborides (TiB2 and ZrB2, etc.), and transition metal nitrides (HfN and TaN, etc.). They possess characteristics such as high melting point, high hardness, and high strength, and are widely used in extreme environments such as aerospace and nuclear energy. Silicon carbide is often added as a second phase to ultra-high temperature ceramics, possessing the ability to inhibit grain growth, improve overall strength, and enhance corrosion resistance.
[0003] The traditional method for preparing ultra-high temperature ceramic-silicon carbide composites involves adding silicon carbide grains to ultra-high temperature ceramic powder and then sintering it. To ensure uniform mixing, further ball milling or mixing processes are required to treat the powder mixture. Furthermore, the controllable range of silicon carbide grain size is limited. Preparing a composite powder with ultra-high temperature ceramic as the core and silicon carbide as the shell would reduce the mixing process, thus simplifying the fabrication process of the composite material's bulk structural components. Moreover, the silicon carbide shell thickness can be adjusted over a wider range, offering significant practical application value. Summary of the Invention
[0004] To address the aforementioned technical problems, the present invention aims to provide a composite powder with ultra-high temperature ceramic core and silicon carbide shell, and its preparation method, thereby achieving uniform coating of ultra-high temperature ceramic particles with silicon carbide.
[0005] In a first aspect, the present invention provides a composite powder with ultra-high temperature ceramic core and silicon carbide shell, wherein the silicon carbide shell is uniformly coated on the surface of the ultra-high temperature ceramic core.
[0006] Preferably, the particle size of the composite powder is 5-500 nm, and the thickness of the silicon carbide shell is 1-50 nm.
[0007] Secondly, the present invention provides a method for preparing the above-mentioned ultra-high temperature ceramic core silicon carbide shell composite powder. The preparation method includes the following steps: dispersing ultra-high temperature ceramic powder in a mixed solution of anhydrous ethanol, ammonia, surfactant and water, ultrasonicating and mechanically stirring to obtain a suspension; continuing to add tetraethyl orthosilicate ethanol solution to the suspension under ultrasonic conditions; after ultrasonication, continuing to add resorcinol and formaldehyde to carry out a room temperature reaction; and then filtering, drying, pyrolysis and carbothermic reduction reaction to obtain the ultra-high temperature ceramic core silicon carbide shell composite powder.
[0008] Preferably, the ultra-high temperature ceramic powder comprises one or more solid solutions of TiC, ZrC, HfC, NbC, TaC, TiB2, ZrB2, HfB2, NbB2, and TaB2, the concentration of ammonia water is 25-28%, and the surfactant comprises hexadecyltrimethylammonium bromide or sodium dodecylbenzenesulfonate.
[0009] Preferably, the volume ratio of anhydrous ethanol to water is 0.5 to 5, the volume ratio of water to ammonia is 5 to 100, the mass ratio of ultra-high temperature ceramic powder to water is 0.01 to 0.5, the mass ratio of surfactant to ultra-high temperature ceramic powder is 0 to 1, and the mechanical stirring speed is 500 to 1000 r / min.
[0010] Preferably, the concentration of the tetraethyl orthosilicate ethanol solution is 0.05–0.2 mol / L, more preferably 0.1 mol / L; the mass ratio of ultra-high temperature ceramic powder to tetraethyl orthosilicate is 0.66–80, the volume ratio of ultra-high temperature ceramic powder to tetraethyl orthosilicate ethanol solution is 1–10 g: 5–400 ml; and the addition rate of the tetraethyl orthosilicate ethanol solution is 1–5 mL / min.
[0011] Preferably, the mass ratio of the ultra-high temperature ceramic powder to resorcinol is 3.12–250, the molar ratio of resorcinol to formaldehyde is 0.24–0.60, and the reaction time at room temperature is 12–24 h.
[0012] Preferably, the drying temperature is 80–100°C; the atmosphere for the pyrolysis and carbothermic reduction reaction is an inert gas, preferably high-purity argon or nitrogen; the temperature for the pyrolysis and carbothermic reduction reaction is 1200–1500°C, and the time is 0.5–1 h.
[0013] Beneficial effects This invention involves coating a layer of silica onto the surface of ultra-high temperature ceramic powder particles by hydrolysis of tetraethyl orthosilicate, followed by coating an organic carbon layer around the silica layer through the polycondensation reaction of resorcinol and formaldehyde, obtaining pre-fired powder in a one-pot process at room temperature, and finally obtaining a composite powder with ultra-high temperature ceramic core and silicon carbide shell through high-temperature pyrolysis and carbothermal reduction reaction. Attached Figure Description
[0014] Figure 1 This is a TEM image of the pre-calcined powder prepared by the "one-pot method" in Example 1 of the present invention. Figure 2 This is a TEM image of the composite powder with titanium carbide core and silicon carbide shell prepared in Example 2 of the present invention. Figure 3 Here is a high-resolution TEM image of the high-entropy (TiZrNbTaHf)C core and silicon carbide shell composite powder prepared in Example 4 of this invention. Figure 4This is a high-resolution TEM image of the composite powder with zirconium diboride core and silicon carbide shell prepared in Example 6 of the present invention. Figure 5 TEM morphology image of the pre-calcined powder prepared by the "one-pot method" in Comparative Example 1; Figure 6 TEM morphology image of the composite powder prepared by high-temperature pyrolysis and carbothermal reduction reaction for Comparative Example 2. Detailed Implementation
[0015] The present invention will be further illustrated by the following embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the present invention.
[0016] First, this invention provides a composite powder with ultra-high temperature ceramic as the core and silicon carbide as the shell. In this composite powder, the silicon carbide shell uniformly coats the surface of the ultra-high temperature ceramic core.
[0017] In some embodiments, the particle size of the composite powder can be 5–500 nm, and the thickness of the silicon carbide shell can be 1–50 nm. Excessively large particle size of the composite powder is detrimental to stirring and dispersion, leading to uneven coating; excessively thick shells are detrimental to the uniformity of the carbothermic reduction reaction, resulting in residual silicon dioxide or abnormal growth of silicon carbide and shell damage.
[0018] The following is an exemplary description of the preparation method of the ultra-high temperature ceramic core and silicon carbide shell composite powder provided by the present invention. The preparation method may include the following steps: dispersing ultra-high temperature ceramic powder in a mixed solution of anhydrous ethanol, ammonia, surfactant, and water, followed by ultrasonication and mechanical stirring to obtain a suspension; adding tetraethyl orthosilicate ethanol solution to the suspension while continuing ultrasonication; after ultrasonication, adding resorcinol and formaldehyde to conduct a room temperature reaction; and then filtering, drying, pyrolysis, and carbothermic reduction reaction to obtain the ultra-high temperature ceramic core and silicon carbide shell composite powder.
[0019] In some embodiments, the ultra-high temperature ceramic powder may include one or a multi-component solid solution of TiC, ZrC, HfC, NbC, TaC, TiB2, ZrB2, HfB2, NbB2, and TaB2, the concentration of ammonia water may be 25-28%, and the surfactant may include hexadecyltrimethylammonium bromide or sodium dodecylbenzenesulfonate.
[0020] Preferably, the volume ratio of anhydrous ethanol to water can be 0.5–5, the volume ratio of water to ammonia can be 5–100, the mass ratio of ultra-high temperature ceramic powder to water can be 0.01–0.5, preferably 0.01–0.25, the mass ratio of surfactant to ultra-high temperature ceramic powder is 0–1, and the mechanical stirring speed is 500–1000 r / min. Controlling the raw material ratios is to regulate the growth rate of the silica shell and the uniform coating of the ultra-high temperature ceramic powder surface.
[0021] In some embodiments, the concentration of the tetraethyl orthosilicate ethanol solution can be 0.05–0.2 mol / L, preferably 0.1 mol / L; the mass ratio of ultra-high temperature ceramic powder to tetraethyl orthosilicate can be 0.66–80; the volume ratio of ultra-high temperature ceramic powder to tetraethyl orthosilicate ethanol solution can be 1–10 g: 5–400 ml; and the addition rate of the tetraethyl orthosilicate ethanol solution can be 1–5 mL / min. This process is the stage of silica shell formation on the surface of the ultra-high temperature ceramic powder. If the amount of tetraethyl orthosilicate ethanol solution is too large or the addition rate is too fast, more silica spherical particles will be generated, introducing impurities.
[0022] In some embodiments, the mass ratio of the ultra-high temperature ceramic powder to resorcinol can be 3.12–250, preferably 3.13–25; the molar ratio of resorcinol to formaldehyde can be 0.24–0.60, preferably 0.50–0.60; and the reaction time at room temperature can be 12–24 hours. This process involves reacting resorcinol and formaldehyde to coat the outermost layer of the ultra-high temperature ceramic powder with organic carbon. The thickness of the organic carbon is controlled to be approximately 2–3 times the thickness of the silica layer, ensuring sufficient carbon and silica to react.
[0023] In some embodiments, the drying temperature can be 80–100°C; the atmosphere for the pyrolysis and carbothermic reduction reactions is an inert gas, preferably high-purity argon or nitrogen; the temperature for the pyrolysis and carbothermic reduction reactions can be 1200–1500°C, and the time can be 0.5–1 hour. This process involves reacting silicon dioxide and an organic carbon shell through pyrolysis and carbothermic reduction to generate a silicon carbide shell. Low reaction temperatures are unfavorable for the carbothermic reduction reaction, while excessively high temperatures can cause Oswald ripening of silicon carbide, resulting in silicon carbide whiskers or large grains that damage the shell structure. The optimal reaction time ensures sufficient pyrolysis and carbothermic reduction reactions.
[0024] This invention employs a room-temperature "one-pot method" to prepare pre-calcined ultra-high temperature ceramic powder with silicon dioxide as the first shell and organic carbon as the second shell. This powder is then subjected to pyrolysis and carbothermic reduction reactions to obtain a composite powder with ultra-high temperature ceramic as the core and silicon carbide as the shell. This preparation method is simple in process and apparatus, and the thickness of the silicon carbide shell can be controlled within a wide range of 1-50 nm.
[0025] The following examples further illustrate the present invention in detail. It should also be understood that the following examples are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention. The specific process parameters, etc., in the following examples are merely examples within a suitable range; that is, those skilled in the art can make appropriate selections within the range based on the description herein, and are not intended to be limited to the specific values in the examples below. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art.
[0026] Example 1
[0027] The preparation method of ultra-high temperature ceramic-core silicon carbide-shell composite powder provided in this embodiment includes the following steps: Step 1: Disperse 10g of ZrC powder in a mixed solution of 50ml anhydrous ethanol, 2.5ml ammonia and 20ml water, and sonicate and mechanically stir at a speed of 1000r / min. Step 2: Slowly add 6 ml of 0.1 mol / L tetraethyl orthosilicate ethanol solution to the suspension at a rate of 1 ml / min. Step 3: Stop the sonication and add 0.04g (3.6×10) to the suspension. -4 0.05 ml (1.3 × 10⁻⁶ mol) of m-diphenol and 0.05 ml (1.3 × 10⁻⁶ mol) of bisphenol A -3 mol) of formaldehyde, and the reaction was carried out at room temperature for 12 hours; Step 4: Filter the powder and dry it in an oven at 100°C. Place the dried powder in a high-temperature furnace at 1500°C under argon protection to carry out pyrolysis and carbothermic reduction reaction, and obtain the ultra-high temperature ceramic core silicon carbide shell composite powder.
[0028] Example 2
[0029] The preparation method of ultra-high temperature ceramic-core silicon carbide-shell composite powder provided in this embodiment includes the following steps: Step 1: Disperse 5g of TiC powder in a mixed solution of 100ml anhydrous ethanol, 4ml ammonia and 20ml water, add 5g of cetyltrimethylammonium bromide surfactant, sonicate and mechanically stir at a speed of 500r / min. Step 2: Slowly add 360 ml of 0.1 mol / L tetraethyl orthosilicate ethanol solution to the suspension at a rate of 5 ml / min. Step 3: Stop the sonication and add 1.6g (1.4×10⁻⁶) to the suspension. -2 mol) of m-diphenol and 2.24 ml (5.8 × 10⁻⁶) -2 mol) of formaldehyde, and the reaction was carried out at room temperature for 24 hours; Step 4: The powder is obtained by filtration and dried in an oven at 80°C. The dried powder is then placed in a high-temperature furnace at 1400°C under argon protection to undergo pyrolysis and carbothermic reduction reactions, resulting in the ultra-high temperature ceramic core silicon carbide shell composite powder.
[0030] Example 3
[0031] The scheme is basically the same as that in Example 1, with the main difference being: In step one, the ultra-high temperature ceramic powder is NbC, and 0.1g of sodium dodecylbenzenesulfonate surfactant is added; In step three, the amounts of resorcinol and formaldehyde added were 0.2g (1.8×10⁻⁶) each. -3 0.25 ml (6.5 × 10⁻⁶ mol) and 0.25 ml (6.5 × 10⁻⁶ mol) -3 mol); In step four, the high-temperature pyrolysis and carbothermic reduction reaction temperature is 1200℃.
[0032] Example 4
[0033] The scheme is basically the same as that in Example 1, with the main difference being: In step one, the ultra-high temperature ceramic powder is high-entropy (TiZrNbTaHf)C; In step three, the amounts of resorcinol and formaldehyde added are 0.2g and 0.25ml, respectively; In step four, the high-temperature pyrolysis and carbothermic reduction reaction temperature is 1400℃.
[0034] Example 5
[0035] The scheme is basically the same as that in Example 1, with the main difference being: In step one, the ultra-high temperature ceramic powder is TiB2; In step three, the amounts of resorcinol and formaldehyde added are 0.2g and 0.25ml, respectively; In step four, the high-temperature pyrolysis and carbothermic reduction reaction temperature is 1300℃.
[0036] Example 6
[0037] The scheme is basically the same as that in Example 1, with the main difference being: In step one, the ultra-high temperature ceramic powder is ZrB2; In step three, the amounts of resorcinol and formaldehyde added are 0.2g and 0.25ml, respectively; In step four, the high-temperature pyrolysis and carbothermic reduction reaction temperature is 1400℃.
[0038] Example 7
[0039] The scheme is basically the same as that in Example 1, with the main difference being: In step one, the ultra-high temperature ceramic powder is HfB2; In step three, the amounts of resorcinol and formaldehyde added are 0.2g and 0.25ml, respectively; In step four, the high-temperature pyrolysis and carbothermic reduction reaction temperature is 1400℃.
[0040] Figure 1 This is a TEM image of the pre-fired powder prepared by the "one-pot method" in Example 1 of this invention. As can be seen from the image, the ZrC ultra-high temperature ceramic powder has a double shell on its surface. The first shell is silicon dioxide with a thickness of ~2.8 nm, and the second shell is organic carbon with a thickness of ~1.7 nm.
[0041] Figure 2 The image shows a TEM image of the composite powder with titanium carbide core and silicon carbide shell prepared in Example 2 of this invention. As can be seen from the image, the silicon carbide shell thickness is ~35.3 nm.
[0042] Figure 3 This is a high-resolution TEM image of the high-entropy (TiZrNbTaHf)C core and silicon carbide shell composite powder prepared in Example 4 of this invention. The image shows that the silicon carbide shell thickness is ~3.7 nm.
[0043] Figure 4 This is a high-resolution TEM image of the composite powder with zirconium diboride core and silicon carbide shell prepared in Example 6 of this invention. The image shows that the silicon carbide shell thickness is 5.3 nm.
[0044] Comparative Example 1
[0045] The scheme is basically the same as that in Example 2, with the main difference being: In step two, 500 ml of 0.1 mol / L tetraethyl orthosilicate ethanol solution is added at a rate of 10 ml / min.
[0046] Figure 5 The image shows a TEM image of the pre-calcined powder prepared by the "one-pot method" in Comparative Example 1. As can be seen from the image, the TiC ultra-high temperature ceramic powder is surrounded by many spherical silica particles.
[0047] Comparative Example 2
[0048] The scheme is basically the same as that in Example 2, with the main difference being: In step four, the high-temperature pyrolysis and carbothermic reduction reaction temperature is 1600℃.
[0049] Figure 6The image shows the TEM morphology of the composite powder prepared by high-temperature pyrolysis and carbothermal reduction reaction in Comparative Example 2. As can be seen from the image, silicon carbide whiskers and other grain shapes are formed. The ultra-high temperature ceramic powder lacks a clear shell at the edges, and the core-shell structure is not obvious.
[0050] Although the present invention has been described in detail through the preferred embodiments above, it should be understood that the above description should not be considered as a limitation of the present invention. Various modifications and substitutions to the present invention will be apparent to those skilled in the art after reading the above description. Therefore, the scope of protection of the present invention should be defined by the appended claims.
Claims
1. A composite powder with an ultra-high temperature ceramic core and a silicon carbide shell, characterized in that, In the composite powder, a silicon carbide shell is uniformly coated on the surface of the ultra-high temperature ceramic core.
2. The ultra-high temperature ceramic-core silicon carbide-shell composite powder according to claim 1, characterized in that, The composite powder has a particle size of 5–500 nm and a silicon carbide shell thickness of 1–50 nm.
3. A method for preparing the ultra-high temperature ceramic-core silicon carbide-shell composite powder as described in claim 1 or 2, characterized in that, The preparation method includes the following steps: dispersing ultra-high temperature ceramic powder in a mixed solution of anhydrous ethanol, ammonia, surfactant and water, ultrasonicating and mechanically stirring to obtain a suspension, adding tetraethyl orthosilicate ethanol solution under ultrasonic conditions, adding resorcinol and formaldehyde after ultrasonication to carry out room temperature reaction, filtering, drying, pyrolysis and carbothermic reduction reaction to obtain the ultra-high temperature ceramic core silicon carbide shell composite powder.
4. The preparation method according to claim 3, characterized in that, The ultra-high temperature ceramic powder includes one or more solid solutions of TiC, ZrC, HfC, NbC, TaC, TiB2, ZrB2, HfB2, NbB2, and TaB2, the concentration of ammonia water is 25-28%, and the surfactant includes hexadecyltrimethylammonium bromide or sodium dodecylbenzenesulfonate.
5. The preparation method according to claim 3 or 4, characterized in that, The volume ratio of anhydrous ethanol to water is 0.5–5, the volume ratio of water to ammonia is 5–100, the mass ratio of ultra-high temperature ceramic powder to water is 0.01–0.5, the mass ratio of surfactant to ultra-high temperature ceramic powder is 0–1, and the mechanical stirring speed is 500–1000 r / min.
6. The preparation method according to any one of claims 3-5, characterized in that, The concentration of the tetraethyl orthosilicate ethanol solution is 0.05–0.2 mol / L, preferably 0.1 mol / L; the mass ratio of ultra-high temperature ceramic powder to tetraethyl orthosilicate is 0.66–80, and the volume ratio of ultra-high temperature ceramic powder to tetraethyl orthosilicate ethanol solution is 1–10 g: 5–400 ml; the addition rate of the tetraethyl orthosilicate ethanol solution is 1–5 mL / min.
7. The preparation method according to any one of claims 3-6, characterized in that, The mass ratio of ultra-high temperature ceramic powder to resorcinol is 3.12–250, the molar ratio of resorcinol to formaldehyde is 0.24–0.60, and the reaction time at room temperature is 12–24 h.
8. The preparation method according to any one of claims 3-7, characterized in that, The drying temperature is 80–100℃; the atmosphere for the pyrolysis and carbothermic reduction reaction is an inert gas, preferably high-purity argon or nitrogen; the temperature for the pyrolysis and carbothermic reduction reaction is 1200–1500℃, and the time is 0.5–1h.
